Retinal differentiation in syngnathids: comparison in the developmental rate and acquisition of retinal structures in altricial and precocial fish species - Alvarez-Hernan, Guadalupe (2020)
The altricial-precocial spectrum describes the degree of morphological maturation of offspring at the moment of hatching. In fishes, precocial species develop all their structures at early stages of embryogenesis and larvae hatch at an advanced stage of development, while altricial species hatch at a less developed stage. The timing of retinal development also varies significantly between precocial and altricial fish species. Thus, retinal development is completed before hatching in precocial species. In contrast, a relatively simple retina is observed in altricial newborns and the acquisition of the adult retinal features extends until late in larval life. Therefore, retinal maturation at hatching could be considered as a morphological character to describe the developmental mode of fish newborns. Syngnathids fishes hatch with well-developed sensory systems, jaws, and feeding structures and, therefore, they are considered as precocial fish species. Using as a model the retina of two species of syngnathids (Syngnathus typhle and Hippocampus guttulatus), we describe the retinal maturity during different embryological stages and compare the results with previous studies in the retina of other altricial and precocial fish species. This will be done through a review of the pertinent literature, as well as by drawing on our own experience gathered through recent studies on fish retinogenesis. These differences in the maturity of the visual system have implications for the vision-based survival skills during the early life stages after hatching and for the overall ecology and fitness of the species.